The cradle dilemma : investing in adoption learning partners - Woodward, Marianne; Bauer, Kathryn; Whitaker, Scott T. ([London] : SAGE, 2016)
As CEO of not-for-profit adoption agency The Cradle, Julie Tye had taken the organization from the brink of dissolution in 1992 to a position of financial stability and health by 2007. One of the innovative steps Tye took in 2002 was to introduce an online learning venture that provided education for families preparing to adopt. The Cradle launched Adoption Learning Partners (ALP), using donated funds and government grants when possible and subsidizing the rest. The income generated by ALP grew from zero in 2002 to approximately $50,000 per month in 2007. But ALP's major market (parents preparing to adopt internationally) was forecasted to decline 50% over the next three years; the Web site was outdated; and new competitors were entering the market. This case study discusses this topic.
Originally Published in: Woodward, M., Bauer, K., & Whitaker, S. T. (2010). The Cradle Dilemma: Investing in Adoption Learning Partners. 5-310-501. Evanston, IL: Kellogg School of Management, Northwestern University.
Description based on online resource; title from home page (viewed on April 28, 2016).
Keywords: elektronické knihy; electronic books; Non-governmental organizations -- Management -- Case studies; Social entrepreneurship -- Case studies